Effective horizontal coordination in coopetitive clusters: developing the required attributes for supply chain management - Wood, Lincoln (MultipliCD, 2010)
The coordination of supply chain management activities between firms in a cluster frequently prove to be challenging when many competitors are present. A challenging form of relationship between members that work together while competing in other markets is known as ‘coopetition.’ Generally, success in the present coopetitive structure may be enhanced through past relationships and disbursement of benefits gained by coordination of activities. Inter-firm coordination of activities between competitors is a horizontal form of engagement, dissimilar to vertical coordination that is frequently studied in supply chain management. These differences are apparent when investigating the barriers to coordination amongst firms in clusters. Complex relationships between members are explored using causal loop diagrams to illustrate the development of the pressures to cooperate or compete. Using a system dynamics approach key variables are identified as leverage points that managers can influence, allowing a more holistic understanding of the long-term impact of decisions.